Prevalence of Taurodontism in Premolars and Molars in the South of Iran - Pegah Bronoosh; Abdolaziz Haghnegahdar; Mehrnoosh Dehbozorgi (Tabriz University of Medical Sciences, 2013)
Background and aims. The study was undertaken to assess the prevalence of taurodontism and related systemic conditions and gender differences in premolars and molars of patients attending Shiraz Faculty of Dentistry. Materials and methods. In this cross-sectional study, panoramic radiographs of 510 randomly selected patients were evaluated by a maxillofacial radiologist for the apically displaced pulp chamber. Detailed medical and family history of the patients was obtained. Results. The prevalence of taurodontism in 510 panoramic views was 5.5% of patients. Females had significantly higher prevalence of taurodontism than men (P>0.05) and mandibular second molar was the most affected tooth. Conclusion. Taurodontism was relatively common in population under study. A family history of other anomalies should be checked for affected patients.